2020
DOI: 10.1155/2020/3598930
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moxibustion on Behavioral Changes and Expression of APP and BACE1 in Hippocampus of SAMP8 Mice

Abstract: Objective. To observe the effect of moxibustion on cognitive function of aging mice, to observe the effect of moxibustion on protein and gene expression of APP metabolism pathway, and to explore the mechanism of action in moxibustion. Methods. 24 SAMP8 were randomly divided into 2 groups (12 in each group): moxibustion group and model group. 12 SAMR1 mice were used as blank controls. Mice in the moxibustion group were treated with moxibustion for 8 weeks, 10 minutes each time, 5 times a week, and for a total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…In addition, moxibustion could alleviate the depression-like behavior and adjust tryptophan transport and 5-HT generation (Li et al, 2019 ). Ha et al ( 2020 ) found that the effect of moxibustion on the cognition of aging mice is associated with the genes and proteins involved in the APP metabolic pathway. Through these mechanisms, moxibustion has good potential in treating cognitive impairment diseases, especially in restraining AD-related Aβ genesis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, moxibustion could alleviate the depression-like behavior and adjust tryptophan transport and 5-HT generation (Li et al, 2019 ). Ha et al ( 2020 ) found that the effect of moxibustion on the cognition of aging mice is associated with the genes and proteins involved in the APP metabolic pathway. Through these mechanisms, moxibustion has good potential in treating cognitive impairment diseases, especially in restraining AD-related Aβ genesis.…”
Section: Introductionmentioning
confidence: 99%
“…10 Elevated expression of BACE1 has been found in senescence-accelerated mouse prone 8 (SAMP8) mice during aging. 11 In addition, it has been shown that inhibition of BACE1 activity may have a negative effect on AD progression by controlling the production of Aβ.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, BACE1 is also related to loss of cognitive function in the central nervous system of development and aging and acts on Aβ N‐terminus and participates in the toxic cracking of APP 10 . Elevated expression of BACE1 has been found in senescence‐accelerated mouse prone 8 (SAMP8) mice during aging 11 . In addition, it has been shown that inhibition of BACE1 activity may have a negative effect on AD progression by controlling the production of Aβ.…”
Section: Introductionmentioning
confidence: 99%